Review of the leafhopper genus Hylica Stål (Hemiptera: Cicadellidae: Hylicinae) with description of one new species - Tang, Jiu; Zhang, Yalin (Zootaxa, 2018)
The leafhopper genus Hylica Stål is reported from China for the first time with its type species H. paradoxa Stål; the male genitalia and the female ovipositor are described and illustrated for the first time. A new species, H. scutealba sp. n., from India is described and illustrated. A key to species of Hylica is provided. H. paradoxa is also recorded from Laos, Nepal, Thailand and Viet Nam for the first time.